Infectious diseases and predominant travel-related syndromes among long-term expatriates living in low-and middle- income countries: a scoping review - Amornphat Kitro; Thundon Ngamprasertchai; Kriengkrai Srithanaviboonchai (Tropical Diseases, Travel Medicine and Vaccines, 2022)
Abstract Introduction Expatriates working in low-and middle-income countries have unique health problems. Migration leads not only to an increase in individual health risk but also a risk of global impact, such as pandemics. Expatriates with no prior experience living in tropical settings have expressed greatest concern about infectious diseases and appropriate peri-travel consultation is essential to expatriates. The objective of this review is to describe infections and travel-related syndromes among expatriates living in low-and middle-income countries. Methods MEDLINE database since the year 2000 was searched for relevant literature. Search terms were “long-term travel”, “expatriate”, and “health problems”. The additional references were obtained from hand-searching of selected articles. Results Up to 80% of expatriates suffered from gastrointestinal problems followed by dermatologic problems (up to 40%), and febrile systemic infection/vector-borne/parasitic infection (up to 34%) Expatriates living in Southeast Asia were at risk of vector-borne diseases including dengue and non-Plasmodium falciparum (pf) malaria while expatriates living in South Asia had a high prevalence of acute and chronic diarrhea. Staying long-term in Africa was related to an elevated risk for pf malaria and gastrointestinal infection. In Latin America, dermatologic problems were commonly reported illnesses among expatriates. Conclusion Certain health risks for expatriates who are going to depart to specific regions should be the focus of pre-travel consultation. Specific health preparations may reduce the risk of disease throughout their time abroad. Disease and symptom awareness is essential for screening, early diagnosis, and better health outcomes for ill-expatriates.